Compulsory and voluntary admission in psychiatric hospitals in northern Norway 2009–2010. A national registry-based analysis. (February 2013) - Norum, Jan; Olsen, Aina; Nybrodahl, Inger; Sørgaard, Knut W.
Abstract Background: During the last decade, Norwegian healthcare authorities have been concerned about the frequent use of coercive measures in psychiatric care. On this background, we aimed to explore the voluntary and compulsory admissions in psychiatric hospitals in northern Norway, the University Hospital of North Norway in Tromsø (UNN-T) and the Nordland Hospital in Bodø (NH-B). Methods: All voluntary and compulsory admissions (2009–2010) among patients aged ≥18 years registered by the Norwegian Patient Registry (NPR) were analyzed retrospectively. Compulsory admission was registered according to the general practitioner's (GP's) decision and the patients were hospitalized in Bodø or Tromsø. A total of 12, 237 admissions and 242, 148 days in hospital were identified. The female/male ratio of admission and stay was 1.17 and 1.15, respectively. Results: The admission rate (northern Norway =1.0) varied significantly from south to north (0.60–1.52). Whereas patients living close to the hospitals had the same admission rate as others, the mean hospital stay was significantly longer (ratio =1.32). Furthermore, the UNN-T had a higher re-admission rate (2% vs. 5%). Municipalities with District Psychiatric Centers (DPC) did not differ from others. A significant difference in the use of coercive measures was revealed between hospitals. Forced medication was the most frequent measure employed. Conclusions: The study documented a south–north gradient in admission rate and indicated differences in the use of coercion. Variation may partly be due to different reporting procedures. This finding and why patients living in the neighborhood of hospitals stay longer should be explored in future studies.